Perlindungan Hukum terhadap Kejahatan Sediaan Farmasi - Bintang Theo Sanjaya; Hery Firmansyah (Jurnal Hukum Lex Generalis, 2024)
Crimes against pharmaceutical preparations are serious crimes, which threaten human rights. Humans who are sick and need treatment for healing become increasingly sick and even cause death. Legal protection needs to be provided to victims who are harmed both criminally and civilly in accordance with the positive law applicable in Indonesia. Although the criminalisation of pharmaceutical preparation crimes has been regulated in Indonesian law, such as in the Health Law, when the case of acute kidney failure caused by contamination of pharmaceutical preparations occurred, many people complained about the performance of the National Food and Drug Agency and the criminal sanctions for the perpetrators and parties responsible for the contamination of pharmaceutical preparations. As in the Constitutional Court Decision Number 106/PUU-XX/2022 which requested to review the punishment and increase the criminal sanctions in the Health Law. This research is conducted using the normative method with deductive specifications, namely analysing from general matters to specific matters, with the aim of ensuring legal certainty against criminal acts of pharmaceutical preparations based on the Constitutional Court Decision.